TRANSLATION OF ARTISTIC AND FIGURATIVE DEVICES AND THE ISSUE OF ACHIEVING EQUIVALENCE (A CASE STUDY OF THE NOVEL A THOUSAND SPLENDID SUNS) - To‘xtanova, Mumtozbegim Ortiqali qizi (Modern American Journals, 2025)
This article analyzes the role of figurative devices in the translation of literary texts, the methods of achieving equivalence when rendering them into another language, and the challenges of preserving their aesthetic and national spirit. Using Khaled Hosseini’s novel A Thousand Splendid Suns as an example, it examines the strategies applied in translating such expressive devices as metaphors, epithets, similes into Uzbek.
Keywords: Literary translation, equivalence, figurative devices, metaphor, epithet, phraseological unit, transformation, national identity.